Analisis Tingkat Kepuasan Anggota dan Strategi Pengembangan Koperasi (Studi Kasus Koperasi Kredit Sehati Jakarta) - Leonardi Pratama; Aida Vitayala S Hubeis; Nora H Pandjaitan (Institut Pertanian Bogor, 2017)
Improving member satisfaction is very important to be taken by credit unions because the cooperative benefit taken from the provision of credit to members. The purpose of this research is (1) determine the level of interest and the level of performance Kopdit Sehati, (2) determine member satisfaction Kopdit Sehati, (3) develop alternative strategies Kopdit pegembangan Sehati. The method used in this study is descriptive analysis, Importance Performance Analysis (IPA), Customer Satisfaction Index (CSI) Internal Factors Evaluation (IFE), External Factor Evaluation (EFE) Analysis Internal External (IE) and the Strengths, Weaknesses, Opportunities and Threats (SWOT). The number of respondents in this studies as many as 100 members of the cooperative. The analysis showed that the overall level of performance Kopdit Sehati (3.98) still does not meet the expected level of interest by members of (4.14). Based on the attributes of IPA obtained priority for repair that Kopdit services using information technology media, availability of information brochures, Kopdit have professional managers, innovation of products offered, the education for members and establish communication with members as well. Based on the calculation of CSI, the service level of 79.78 percent Kopdit Sehati. This means that the level of satisfaction index Sehati Kopdit member located between the range of 0.66 to 0.80, which means members are satisfied with the performance of services Kopdit Sehati. After weighting and scoring through IFE matrix (2.64) and matris EFE (2.86). IE matrix shows that the position Kopdit Sehati is in cell V, can be managed with a strategy to maintain and sustain namely by using market penetration strategies and product development could be the most appropriate for Kopdit Sehati. The development strategy Kopdit Sehati generated from SWOT Matrix and QSPM obtained five priorities suggested strategies are: (1) Development of branch offices and place of service members, (2) Innovation product savings and loans (3) Increase the dissemination of cooperatives to the community, (4) Increases number of employees, and (5) Increase the effective promotion activities.